Evaluation of surface physical properties of acrylic resins for provisional prosthesis - Sérgio Paulo Hilgenberg; Emigdio Enrique Orellana-Jimenez; Wilmer Fabian Sepúlveda-Navarro; Beatriz Elena Arana-Correa; Dario César Teixeira Alves; Nara Hellen Campanha (Materials Research, 2008)
Acrylic resins used for provisional prostheses should have satisfactory superficial characteristics in order to ensure gingival health and low bacterial attachment. The purpose of the present study was to evaluate the superficial roughness and contact angle after two types of polishing and the Vickers hardness of three acrylic resins (Duralay - G1, Dencrilay - G2, and Dencor - G3), all shade 66, indicated for provisional fixed prostheses. Five 20 x 3 ± 1 mm diameter discoid specimens were obtained for each group. One side of the specimens was subjected to standard polishing (pumice and whiting slurry), and the opposite side was polished with special tips. The mean roughness and contact angles of the materials were measured. The specimens were subjected to the Vickers microhardness test, which indicated that standard polishing produced a surface roughness equivalent to that of the special tips. The contact angles obtained with the standard polishing were equivalent to those observed in the special tips group. The microhardness of G1 and G3 resins showed statistical differences.